Quantification of bioactive compounds from Averrhoa Bilimbi - Siti Aishah, Muhmed (2013)
Averrhoa bilimbi has been widely used in traditional medicine, thus, this fruits have received much attention because of its nutritional and antioxidant properties. The purposes of this study are to determine the bioactive compounds in averrhoa bilimbi and to study their optimum parameters during extraction. Antioxidant activity of the averrhoa bilimbi extract was determined based on 2,2-diphenyl-1-picrylhydrazyl freeradical (DPPH·), total phenolic content was measured using Folin–Ciocalteu reagent, while flavonoids is determined spectrophotometrically. Solvent extraction selected is methanol (50%) where this condition has yielded total flavonoids content is about 568.75 μg/ml QE. The highest antioxidant capacities measured is 80.02 % and total phenolic content shows about 175.3 mg/mL GAE.In this study, 60 minutes extraction time generally showed the highest effect on total flavonoids which is 496.25 μg/ml QE. Averrhoa bilimbi extraction had total phenolic about 164.7 mg/mL GAE and antioxidant activity is around 74.5%. 70° C extraction temperature shown the best extraction for total phenolics at 127.7 mg/ml GAE, while achieved highest total flavonoids at 656.25 μg/ml QE and the highest for DPPH radical scavenging activity is found about 70.05%. From the effect of agitation speed, 300 rpm achieved the highest value for total phenolics, total flavonoids and antioxidant capacity, DPPH which is about 193.3 mg/ml GAE, 717.75 μg/ml QE, and 77.03% respectively. Overall, based on the ideal extraction conditions chosen, optimum level of TPC, TFC and antioxidant capacity were obtained in averrhoa bilimbi fruit extract. The selected extraction conditions could be used for further studies and functional food product development.